If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = 1 + x Solving 4 = 1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 4 + -1x = 1 + x + -1x Combine like terms: x + -1x = 0 4 + -1x = 1 + 0 4 + -1x = 1 Add '-4' to each side of the equation. 4 + -4 + -1x = 1 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 1 + -4 -1x = 1 + -4 Combine like terms: 1 + -4 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3
| 9s+5t+6=0 | | 4(x-3)+2=5-2(x+1) | | 5x-49y= | | x*2=4*x-2 | | 157.5n+2n= | | 2(-1+5v)=8v-16 | | 5(-6)=-5(30) | | 5(-6)=5(30) | | 10y-10x=3y-3x | | v(50)=5.2+2.5(50) | | 5x^2-36x-16=0 | | B=4x-2x+5 | | 5(5-11)+5(17+13)=5 | | 2x^3+x^2-24x-12=0 | | 42=2r+6r-10+6 | | 4(6y-y)=75 | | 21=3(y-1)+y | | 1-9a=127 | | 2-8(1+5m)=-206 | | (3x+5z)(5x-7z)= | | 2x^2+312-50x=0 | | 3p-8q=5 | | 9y=-7.5x+33 | | -3=10a-10 | | x+y+40=180 | | 5tanx+3=4 | | x+2/2=-4 | | -4(4-x)=3(x-6) | | 5p-9q=17 | | -7(-8)= | | 5x^2+36x+24=0 | | 4x+3y=9y-5x |